Blue lily, lily Blue - Stiefvater, Maggie, 1981- (2014)
Blue Sargent has found things. For the first time in her life, she has friends she can trust, a group to which she can belong. The Raven Boys have taken her in as one of their own. Their problems have become hers, and her problems have become theirs. The trick with found things though, is how easily they can be lost
Keywords: Paranormal fiction; Dreams -- Juvenile fiction; Family secrets -- Juvenile fiction; Magic -- Juvenile fiction; Young adult fiction